2019
DOI: 10.1177/0959683619862036
|View full text |Cite
|
Sign up to set email alerts
|

Convergent catastrophes and the termination of the Arctic Norwegian Stone Age: A multi-proxy assessment of the demographic and adaptive responses of mid-Holocene collectors to biophysical forcing

Abstract: Using multiple archeological and paleoenvironmental proxies, this paper makes the case for a climate-induced convergent catastrophe among the human population of terminal Stone Age Arctic Norway. We show that climatic changes correlate with the termination of the so-called Gressbakken phase (4200–3500 cal BP), and unpack the middle-range mechanisms linking the Gressbakken termination to contemporaneous changes in the biophysical environment. We show that what was a Holocene extreme, and likely volcanically-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…Detailed scrutiny of the mid-Holocene population cycle and regional differentiation has demonstrated that it entailed considerable coastal packing and coincident population depletion in the interior (Hood et al In press;Jørgensen and Riede 2019). A wider comparative study showed that the human ecodynamics identified in Arctic Norway occurred in synchrony with a maritime adaptive specialization across northern Fennoscandia (Jørgensen et al 2020) along with analogous population dynamics in adjacent areas (Tallavaara et al 2010;Tallavaara and Pesonen 2018;Tallavaara and Seppä 2012).…”
Section: Ecodynamic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed scrutiny of the mid-Holocene population cycle and regional differentiation has demonstrated that it entailed considerable coastal packing and coincident population depletion in the interior (Hood et al In press;Jørgensen and Riede 2019). A wider comparative study showed that the human ecodynamics identified in Arctic Norway occurred in synchrony with a maritime adaptive specialization across northern Fennoscandia (Jørgensen et al 2020) along with analogous population dynamics in adjacent areas (Tallavaara et al 2010;Tallavaara and Pesonen 2018;Tallavaara and Seppä 2012).…”
Section: Ecodynamic Settingmentioning
confidence: 99%
“…Crucially, the mid-Holocene population peak corresponds to what was also a forest maximum, with forest coverage on the coast, greatly exceeding current conditions (Sjögren and Damm 2019). In response, the presence of sedentary ecotype, forest reindeer close to the coast has been suggested and argued to have reinforced the coastal settlement packing (Hood In press;Jørgensen and Riede 2019). This would undercut the need for mobility patterns into the interior as all necessary resources were available at the coast and thus facilitate increased sedentism.…”
Section: Ecodynamic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…2018; Damm et al . 2019; Jørgensen and Riede 2019; Tallavaara and Pesonen 2019) over the last decades.…”
Section: Methodsmentioning
confidence: 99%
“…The relevance of past demography for understanding culture change in prehistory specifically has long been recognised 2,3 . Demographic conditions impinge on cultural transmission [4][5][6] but are also clearly implicated in the boom-and-bust patterns of population fluctuations -including periodic extirpations -suggested to have characterised the demographic histories of prehistoric foragers and incipient farmers in many regions [7][8][9][10] . Numerous recent studies have focused on the drivers of population expansion to explain the pattern and timing of human colonisation using a variety of ecological comparative approaches 11,12 (but see ref.…”
Section: Introductionmentioning
confidence: 99%